Wpływ pełzania betonu na sprężone ustroje prętowe - CHUDZIKIEWICZ, Andrzej (Engineering Transactions, 1956)
Concrete creep in prestressed beam structuresThis paper is concerned with some general methods of solution of problems under consideration.In the first section the theoretical foundations are discussed according to Dischinger's theory of creep. In the second section structures prestressed with non-grouted cables are considered. A solution is obtained by means of the system (2.1.3) of differential equations for statically determinate, and the system (2.2.1) for statically indeterminate structures. The unknown functions of creep modulus φ are force changes in cables and the redundant forces.For practical purposes the solution by means of power series (2.3.1) is convenient. The coefficients xk,r are determined from the system of equations (2.3.3). Sufficient exactness for φ < 4 is obtained with two terms, for small values of φ one term is often sufficient.In the third section structures prestressed with grouted cables are considered. In the first part, solution in the form of a series as well as an approximate solution are given for statically determinate structures. In the second part a general theory of statically indeterminate structures is developed. In order to find the redundant forces Xk(φ) a system of integral equations (3.2.7) is established. The functions δi0(φ) represent the influence of plastic deformations due to the initial load (M0b and N0b), and the functions δik(φ) – the influence of plastic deformations due to the permanently acting redundant force Xk = 1. The solution of the system (3.2.7) is assumed in the form of the power series (3.2.10). The convergence of the series xk,r is slow in general; more rapidly convergent series wk,r are olbtained using (3.2.12), where the coefficient μk should be assumed according to (3.2.13). For a degree of exactness of several percent two or three terms of the series wk,r are, in general, sufficient. The procedure, for statically indeterminate structures is illustrated by the numerical example 7. The first two tables present the computation of the changes ΔM0b and ΔN0b of internal forces in the basic system ~ith the assumption that the redundant quantities X1(φ) are equal to zero. The next tables are devoted to the computation of a redundant! quantity and its influence on the internal forces of the structure ΔM(X)b and ΔN(X)b. In practice however the second part of the calculation can be reduced by some 30 to 50 percent.In the fourth section „combined” structures are discussed as well as the influence of reinforcement and the problem of friction in structures prestressed with non-grouted cables.